Effects of hindlimb suspension on development of proximal and distal femur morphological abnormalities in growing rats. Issue 2 (13th May 2022) - Ozawa, Junya; Kaneguchi, Akinori; Ezumi, Shun; Maeno, Takuma; Iwazawa, Jukiya; Minanimoto, Kengo; Ikeda, Airi
Abstract: Although morphological abnormalities of the femur are known predisposing factors for numerous musculoskeletal disorders, the etiology of these abnormalities is poorly understood. This study aimed to investigate whether femoral morphogenesis is affected by hindlimb suspension (HS) in growing rats. We used 41 four‐week‐old female rats in this study. In the HS groups, rats were suspended from their tails for 2, 4, and 8 weeks. Age‐matched animals were used as controls. We examined morphological indices of the femur using three‐dimensional reconstructed images from X‐ray computed tomography. The femoral neck anteversion angle (AVA) was higher with growth in the experimental groups and did not differ in control groups. The AVAs in the HS groups were larger than controls at any time point. In the control groups, the trochlear angle (TA) was higher, rotating inward with growth, but did not differ in the HS groups. The TAs in the HS groups were smaller and rotated more outward compared with the control groups at any time point. The height ratios of the medial and lateral condyles (MC/LC), an asymmetry index, were larger in the HS groups compared to controls at any time point. There were strong relationships between proximal (AVA) and distal morphologies, such as the TA (Spearman's coefficient [ r s ] = −0.80, p  < 0.001) and MC/LC ( r s  = 0.79, p  < 0.001). Our data suggest that sufficient physical activity in early life may protect against morphological femur abnormalities associated with hip and knee joint diseases. Abstract : Morphological femur abnormalities are associated with both hip and knee joint disorders. We revealed that hindlimb unloading in growing rats induced femoral morphologies associated with several musculoskeletal disorders, such as increased femoral neck anteversion, suppression of increased trochlear angle, asymmetric condyle growth, and decreased trochlear groove width. Our data suggest that sufficient physical activity in early life may be effective as the protective measures against hip and knee joint diseases.